The Effect Of Online Shop The Level Of Product Sales In The Sengkang City Central Market, Tempe District, Wajo Regency - Nurul Hidayat; Haedar Akib; Aris Baharuddin; Henni Zainal (Public Resource Innovation Management and Excellence, 2024)
This study aims to find out how the influence of the Central Market of Sengkang City, Tempe District, Wajo Regency. This research uses quantitative research methods. Data collection techniques use are through observation, questionnaires and documentation. The research is a many as 77 traders at the Central Market of Sengkang City who have used an online shop to market product. The data obtained from research results were processed using data analysis and using the SPSS 25 application consisting of validity and reliability. Tebuk descriptive data analysisi and inferential statistical analysis. The results show that the indicators used in each of these variabels show that the online shop variabel and the level of sales at the Central Sengkang Market, Wajo Regency have a significant influence. Online shop with a strong sales level. And the coefitient of determination R test was obtained at 0,345 which means that the influence of the online shop on the level of product sales at the Sengkang Central Market, Wajo Regency, obtained value of 34,5%, while the remaining 65,5% was influenced by other factors.